Effect of fat source and level on finishing pig performance - David A Nichols; Joe D Hancock; Jim L Nelssen; Robert H Hines; Donald H Kropf (Kansas Agricultural Experiment Station Research Reports, 1991)
Two hundred and forty finishing pigs were utilized to evaluate the effect of fat source and level on growing pig performance and carcass characteristics. Pigs were fed a milo-soybean meal diet balanced on a constant energy:lysine and energy:protein ratio. Dietary treatments were: 1) control; 2,3,4) 2.5, 5.0, or 7.5% added soybean oil; 5 and 6) 5.0 or 7.5% added tallow. In comparing pigs fed soybean oil to tallow, there were no significant effects on feed intake, average daily gain, or feed to gain ratio. Soybean oil additions compared to tallow resulted in carcasses with significantly more average backfat as well as 10th rib fat depth. In addition, carcass firmness was significantly reduced as level of soybean oil addition was increased compared with tallow addition.; Swine Day, Manhattan, KS, November 21, 1991
Keywords: Swine day; 1991; Kansas Agricultural Experiment Station contribution; no. 92-193-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 641; Swine; G-F; Performance; Fat; Source; Carcass